Autoimmune Hemolytic Anemia (AIHA): Response to first line therapy in patients treated at tertiary care centre - Jahanzeb ur Rehman; Jahanzeb ur Rehman; Asghar Ali Kerio; Raheel Iftikhar; Uzma Rahim; Sahla Riaz (Medical Journal of South Punjab, 2024)
Objective: To determine the response of First line therapy in patients with AIHA.Methods: Eighty individuals of various age groups with AIHA were included. Prednisolone was administered as first line treatment in maximal dose of 1-2mg/kg/day. The initial response of hemoglobin was assessed on day 14 and subsequently every two weeks until the full response was attained. Numerical variables i-e age, duration of response, hemoglobin (Hb), lactate dehydrogenase (LDH), indirect bilirubin were assessed by mean ±SD. Categorical variables i-e direct antiglobulin test (DAT), gender, response (complete response, partial response, no response), were analyzed for frequency and percentages.  Data was stratified for age, gender, duration of response; Hb, LDH, Total bilirubin and DAT. Variables with p value ?0.05 were considered statistically significant.Results: The median age of the patients was 34.5 years. 38 male and 42 were female. 77 had a positive DAT, and 49 had both direct and indirect Coombs tests positive. The major symptoms reported was generalized weakness (61.3%) followed by progressive pallor (27.5%). Our study, revealed overall response rate 76.3%. An analysis was performed to assess the correlation between response to first-line therapy and various variables, including gender, co morbidities, visceromegaly, RCC ransfusion and blood counts which did not reveal any statistically significant correlation. The median duration of response to steroids was 13 months. During the study period, n=61 (76.3%) patients were alive, n=12 (15.0%) patients passed away, and n=7 (8.8%) patients lost to follow-up.Conclusion: our study highlights the effectiveness of oral Prednisolone as a first-line therapy in AIHA, with a 76.3% response rate. However, non-responsiveness to steroids remains a challenge, and patient demographics do not seem to directly impact treatment outcomes.